MULTICOLOR PHOTOMETRY OF STELLAR AGGREGATES - MENDOZA, EUGENIO (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1968)
We have made multicolor photometric observations over the range of wavelength from 0.36 microns in the ultraviolet to 5.0 microns in the infrared, on 1063 stars in the regions of h and x Persei, Pleiades, Hyades, Orion, Praesepe M 67, Scorpio-Centaurus, C
BOL OBS TONAN TACUB
Keywords: MULTICOLOR, PHOTOMETRY, STELLAR, AGGREGATES; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS